Zoonotic links of coronavirus SARS-CoV-2 - Iannacone, José (2020)
On March 11, 2020, the World Health Organization (WHO) declared COVID-19 as a pandemic illness. As of April 21, 2020, 2,528,396 positive cases and 174,547 deaths from SARS-CoV-2 / COVID-19 have been registered worldwide in 210 countries and territories. It has been suggested that the disease can be transmitted zoonotically from animals to humans. The objective of this review work was to analyze what was published in relation to the zoonotic link of COVID-19. SARS-CoV-2 is closely related to a bat coronavirus, which was identified in Rhinolophus affinis Horsfield, 1823, in China’s Yunnan province, where COVID-19 was started. A comprehensive analysis of mammal-host-virus relationships has shown that bats harbor a significantly higher proportion of zoonotic viruses than other orders of mammals. The pangolin Manis javanica Desmarest, 1822, is the main suspect of being the intermediate host, because when comparing its viral genetic material with that of SARS-CoV-2 it showed a high similarity. In relation to domestic animals, ferrets and cats have been found to be susceptible to infection. In contrast, it replicates poorly in dogs, and SARS-CoV-2 is not susceptible in pigs, chickens, and ducks. Similarly, there is no accurate evidence to suggest that infected pets have a role in the spread of COVID-19 to humans.